Cochlear Implantation with Fontan Circulation: A Rare Case of Non-Cardiac Pediatric Surgery - I Made Bhasma Adiyana; I Putu Kurniyanta (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2024)
Background: Fontan circulation is a cardiac circulation following the Fontan procedure in patients with a single ventricle congenital heart defect. This circulation depends on the difference in pressure between pulmonary capillaries and central venous pressure to achieve optimal cardiac output. This case report aims to discuss intraoperative anesthesia management in a patient with Fontan circulation undergoing a non-cardiac surgical operation. Case presentation: The patient is a 7-year-old male with a history of congenital heart disease who has undergone the Fontan circulation procedure and is now undergoing Cochlear implantation surgery. The patient was managed with general anesthesia - endotracheal intubation and controlled ventilation during the operation, following the principle of minimizing intrathoracic positive pressure, low PEEP, and low tidal volume with a target peripheral saturation > 95%. Cardiac output monitoring during the intraoperative period is done using intra-arterial blood pressure. After 5 hours of surgery, the patient was extubated with stable hemodynamics. Conclusion: The primary goal of intraoperative anesthesia management in patients with Fontan circulation is to maintain an optimal transpulmonary gradient by ensuring optimal transpulmonary blood flow, thus preserving cardiac output.